Conflicting Voices in HIV/AIDS Education of the South African Youth: School Culture Versus South African Traditional Healers Using Ancestral Worship - Siwela, Miriam; Jansen, Cecelia (International Journal of Criminology and Sociology, 2016)
The United Nations Agency of International Development (2013) states that an estimated 24.7 million people are living with HIV in sub-Saharan Africa, nearly 71% of the global total. The 2.9 million are young people aged 15–24 and this generation is living in South Africa. These alarming statistics reveal that various HIV/AIDS prevention strategies have met limited success. The question arises: why? The South African youth face the dilemma that they receive conflicting messages from two opposing sources, each with a strong persuasive pull of its own where HIV/AIDS education is concerned. On one hand, the voice of modern medical science proclaims that the disease is caused by a viral infection that suppresses the victim’s immune response, while on the other hand spiritual voices of African traditional healers offer explanations such as witchcraft or angry ancestors. This article is an attempt to discover whether either or neither of these voices is gaining ground amongst the youth. This article is based on a qualitative phenomenological study conducted at an urban secondary school in Pretoria, South Africa. Empirical findings resulted from the purposive sampling by means of interviews conducted with two focus groups of teachers, three focus groups of grade 12 school learners and one school principal. This was followed by thematic analysis involving the identifying, analysing and reporting patterns (themes) within data. Facts emerging from the research were that conflicting voices are stressful for young people who are subjected to societal pressure to conform and comply with unrealistic expectations. The South African social culture of ancestral worship is very powerful, yet school culture has significant countervailing influence that sheds liberating “light” where gloom of fear, uncertainty and superstition used to prevail. It is critical to note in this regard, for instance, that where HIV/AIDS remedies are concerned, there is no standardised solution for the ‘entire world’ and that a unique situation prevails in the South African social cultural environment where ancestral worship exerts a critically real influence on people’s response to the threat of HIV/AIDS.